Secure Cloud Processing for Smart Meters Using Intel SGX - Araújo, Marcos V. M.; Prado, Charles B. do; Carmo, Luiz F. Rust C.; Rincón, Alvaro E. R.; Farias, Claudio M. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2018)
Smart Grids are power grids that use Information and Communication Technologies to improve the power generation, transmission and distribution. The main characteristic on Smart Grids is the ability to process and transmit a huge data information in real-time. However, that rise a new security challenge on confidentiality and data integrity, due to Smart Grids can be part of hostile environments. For example, using a cloud computing to realize billing and load balance process. Thus, to ensure confidentiality and data integrity of Smart Grids in cloud environments, this paper proposes an application for the protection of billing and load balancing data using the Intel Intel Software Guard extension SGX platform. SGX allow to instantiate protected memory areas called enclaves, preventing subprocesses or other machines within the cloud from accessing the data stored in them.